INFLUENCE MASS OF THE RINGS, RESILIENTLY SET ON DISK, ON DYNAMIC DESCRIPTIONS OF HYDROSTATODYNAMIC BEARING OF THE DOUBLED TYPE - Владимир Иосифович Назин (Авіаційно-космічна техніка та технологія, 2020)
The task is to develop recommendations for the design of dual-type hydrostatodynamic plain bearings based on the existing experience in designing this type of plain bearings, as well as based on many theoretical and experimental studies performed by the author of this work. The number of the most necessary parameters for the design of dual-type hydrostatodynamic bearings is determined. Particular attention was paid to the development of recommendations for additional parameters specific to the design of double type plain bearings. Attention is paid to the selection of double-type bearing materials and it is shown that the problem of selecting materials for hydrostatic dynamic bearings is not so relevant, however, sometimes in start-up and shutdown modes, as well as in emergencies, to ensure high reliability of the designed machine, it is necessary to pay attention to the choice of bearing materials. The influence of various forms of chambers on the static and dynamic characteristics of hydrostatodynamic bearings is analyzed and it is shown that the greatest distribution in practice, they got rectangular cameras. It is shown that the flow regime of the working fluid also significantly affects both the static and dynamic characteristics of the bearing. It is noted that even with a non-rotating rotor in a hydrostatodynamic bearing, the most turbulent mode of flow of the working fluid is most often observed. The influence of the thickness of the working fluid layer on increasing the rigidity of the supports and expanding the range of stable operation is considered. It is shown that with a decrease in the clearance in the bearing, its bearing capacity increases and the range of stable operation expands, however, this increases the friction power loss, increases the likelihood of clogging of the slit bearing path, and also increases the requirements for the quality of manufacture of the bearing working surfaces. It is recommended that in the double hydrostatodynamic bearing in the outer and inner parts to assign the same clearances. It is shown that in a dual hydrostatodinamic bearing, the existing recommendation on the number of chambers can lead in some cases to large working fluid flow.